2016
DOI: 10.1016/j.compstruct.2016.01.093
|View full text |Cite
|
Sign up to set email alerts
|

Design and evaluation of an integrated FRP composite wicket gate

Abstract: Hydraulic gates need to be lightweight , corrosion-resistant, maintenance-free, and durable with high endurance under fatigue loads. All of these requirements could be challenges to be met using conventional materials like steel and concrete. However, with the emergence of advanced Fiber Reinforced Polymer (FRP) composites for waterway structures, it has now been possible to achieve all of these physical and performance requirements in a cost-effective manner. Due to their lightness, excellent corrosion and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The decomposition rate slows down significantly in the third stage, and eventually the quality of the samples with different aging times shows differences, mainly due to two reasons: firstly, because of the evaporation of water from the aged samples, and secondly, because of the degradation of some of the resins already present in the adhesive after the aging process. From the graph, it can be observed that the decomposition temperature of the samples in different aging environments is almost the same; in the salt solution experimental conditions this did not change the thermal stability of the adhesive significantly [40]. This can be demonstrated by the final remaining mass.…”
Section: Tga-dtg Resultsmentioning
confidence: 85%
“…The decomposition rate slows down significantly in the third stage, and eventually the quality of the samples with different aging times shows differences, mainly due to two reasons: firstly, because of the evaporation of water from the aged samples, and secondly, because of the degradation of some of the resins already present in the adhesive after the aging process. From the graph, it can be observed that the decomposition temperature of the samples in different aging environments is almost the same; in the salt solution experimental conditions this did not change the thermal stability of the adhesive significantly [40]. This can be demonstrated by the final remaining mass.…”
Section: Tga-dtg Resultsmentioning
confidence: 85%
“…39 Although using FRPCs to manufacture runners is a high impact area, FRPCs offer similar advantages for other hydropower components as well. Other potential applications for FRPCs for hydropower components include composite bearings, 40 41 composite pipelines or conduits (Kasharin et al 2015), and composite wicket gates (Vijay et al 2016). In 2016, the US Army Corps of Engineers sponsored a project exploring using glass FRPCs to replace timber wicket gates.…”
Section: Innovative Materialsmentioning
confidence: 99%
“…In water conservancy projects, sluice gates have been widely used for retaining water (Vijay et al 2016). As a type of water-retaining construction, there is more than one hundred years of history for the existence of the bottom shaft driving flap gate, a form of dam gate with special structures.…”
Section: Introductionmentioning
confidence: 99%
“…It not only has important academic significance, but also relates to key technologies of the project, so river problem research has important meaning. Vijay et al (Vijay et al 2016) conducted the design and evaluation of an integrated fiber reinforced polymer (FRP) composite wicket gate, and the authors introduced the advanced method of FRP to study the issues of hydraulic gates. It is also well-known that FRP is a cost-effective method to achieve the physical and performance requirements in engineering (Soti 2014;Rossum 2015).…”
Section: Introductionmentioning
confidence: 99%